Deterrence and Diplomacy: Investigating India’s Motives Behind Conflict Deferment and Pakistan’s Endeavors at Conflict Resolution - Dr Zia Ul Haque Shamsi (CISS Insight Journal, 2023)
The doctrine of Mutually Assured Destruction (MAD) established by superpowers of the Cold War era, ensured that there was no war in which their forces were directly involved. Proxy wars between them continued with overt support of rivals in different regions. Hence, both camps established and maintained strategic stability, while paradoxically instability persisted at the tactical level, with the latent risk of a full-fledged war. After closely watching and analyzing the dynamics of nuclear deterrence between the Cold War era super-powers, a consensus emerged among scholars of international relations that nuclear deterrence, between the two nuclear weapon states, ensured the avoidance of war. In the South Asian context, deterrence was overtly established in 1998 after Pakistan responded to India’s resumption of nuclear weapons tests. However, limited military engagements on the periphery continued periodically. Thus, the possibility of border crisis and aerial skirmishes exist. These crises could potentially escalate horizontally and vertically to a level that leaves little space for diplomacy or deterrence to work in concert or independently. This paper analyzes the linkages between deterrence and diplomacy, India’s motives for conflict deferment, and Pakistan’s efforts to move from conflict management to conflict resolution through diplomatic channels to minimize the probability of military confrontations.